Participatory and Conventional Biodiversity Assessments: Creating Awareness for Better Natural Resource Management - Dixit, Sreenath; Tewari, J C; Wani, S P; Vineela, C; Chausrasia, A K; Panchal, H R (Annals of Arid Zone, 2016)
Common grazing land in a cluster of villages of Bundi district in the hot semi-arid region of eastern Rajasthan, was degraded due to high grazing pressure. A community initiative, facilitated by an NOD, regenerated half of the grazing land by adopting social and biophysical interventions. A participatory assessment of the regenerated and the degraded grazing land, involving a team of ecologists, microbiologists and community members was undertaken to know the impact of the collective action. This paper discusses the results of the assessments and argues that community initiatives combining social and biophysical measures can yield best results to raise awareness of the communities for rehabilitation and conservation of biodiversity in fragile ecosystems. Key words: Participatory, conventional, biodiversity, grazing land, rehabilitation.